Homogeneously dispersed composites of hydroxyapatite nanorods and poly(lactic acid) and their mechanical properties and crystallization behavior. (May 2020) - Zhang, Rong; Hu, Hailong; Liu, Yang; Tan, Junjun; Chen, Wenqi; Ying, Cheng; Liu, Qingting; Fu, Xudong; Hu, Shengfei; Wong, Ching Ping
Graphic abstract: Highlights: HA nanorods dispersed as single particles without aggregation in PLA matrix. The elongation at break of the composites increased from 4.24% to 8.79% by adding HA nanorods, whereas the tensile strength and Young's modulus were largely unchanged. HA nanorods accelerated evidently the PLA crystallization rate and induced a transition to an ordered crystalline morphology. Abstract: Aiming to disperse HA nanocrystals in a polymer matrix homogenously, uniform oil-soluble HA nanorods were synthesized via an oleic acid (OA)-assisted mixed-solvent thermal method, and then poly(lactic acid) (PLA)/HA nanorods nanocomposites were fabricated by using a solution method. The HA nanorods with an OA monolayer on the surface dispersed homogeneously in organic solvents and the dispersion in polymer solution was transparent and colloidally stable. TEM images showed that HA nanorods dispersed as single particles without aggregation in PLA matrix. The elongation at break of the composites increased from 4.24% to 8.79% by adding HA nanorods, whereas the tensile strength and Young's modulus were largely unchanged. HA nanorods accelerated evidently the PLA crystallization rate even at a low HA loading and induced a transition to an ordered crystalline morphology confirmed via non-iso/isothermal crystallization, the spherulitic morphology, calculations and wide-angle X-ray diffraction during heating and cooling cycles.